Criteria for the legal protection of animals in the legislation and comparative jurisprudence - Morales, Guisseppi (2023)
The protection of animals is one of the increasingly intense concerns in various parts of the world that is reflected in the legislative and jurisprudential production of States. In this sense, the aim of this research was to analyse the criteria that have been developed in the legislation and in the reflection of the justice administration bodies of Latin American and European countries. It was identified that there are innovative criteria that allow assigning animals the quality of sentient beings and in some cases as subjects of law, which allows expanding the scope of protection in favor of them.